Analysis of the Impact of Rubber Latex Price Decline on the Welfare of the Community in Surulangun Village, Rawas Ulu Subdistrict, Indonesia - Febrina Nur Annisa; Widya Analisa (Jurnal Riset Perkebunan, 2025)
The price of rubber latex is one of Indonesia’s leading plantation commodities. This phenomenon directly affected the welfare of farmers, particularly in Surulangun Village, North Musi Rawas Regency, where the majority of residents depend on rubber plantations for their livelihood. This study aims to analyze the impact of falling rubber prices on farmers’ income, consumption patterns, and adaptation strategies, while also providing relevant policy recommendations. The research employed a mixed-methods approach. Quantitative data were collected through a survey of 40 household heads of rubber farmers, while qualitative data were obtained through in-depth interviews, field observations, and documentation. The sampling technique used was purposive sampling, with the criteria of farmers who had been working for at least five years. Quantitative data were analyzed using the Wilcoxon Signed-Rank Test to examine the differences before and after the price decline, whereas qualitative data were analyzed thematically with triangulation validation. The results revealed a significant decline in three main welfare indicators. The average income of farmers decreased from IDR 3,000,000–5,000,000 to IDR 1,500,000–2,000,000 per month. Food consumption dropped by up to 37.5%, with a shift toward cheaper staple foods. Non-food consumption, such as education and healthcare, also declined drastically. Most farmers coped with the situation by engaging in side jobs, such as daily labor or small-scale trading. The study concludes that the decline in rubber prices has had a serious impact on farmers’ household welfare. Policy implications include the need for income diversification, the establishment of a minimum rubber price, food subsidies, and the strengthening of farmers’ institutional capacity to build more sustainable rural economic resilience.